VEGF receptor‐2/neuropilin 1 trans‐complex formation between endothelial and tumor cells is an independent predictor of pancreatic cancer survival. Issue 3 (4th September 2018) - Morin, Eric; Sjöberg, Elin; Tjomsland, Vegard; Testini, Chiara; Lindskog, Cecilia; Franklin, Oskar; Sund, Malin; Öhlund, Daniel; Kiflemariam, Sara; Sjöblom, Tobias; Claesson‐Welsh, Lena
Abstract: Unstable and dysfunctional tumor vasculature promotes cancer progression and spread. Signal transduction by the pro‐angiogenic vascular endothelial growth factor (VEGF) receptor‐2 (VEGFR2) is modulated by VEGFA‐dependent complex formation with neuropilin 1 (NRP1). NRP1 expressed on tumor cells can form VEGFR2/NRP1 trans ‐complexes between tumor cells and endothelial cells which arrests VEGFR2 on the endothelial surface, thus interfering with productive VEGFR2 signaling. In mouse fibrosarcoma, VEGFR2/NRP1 trans ‐complexes correlated with reduced tumor vessel branching and reduced tumor cell proliferation. Pancreatic ductal adenocarcinoma (PDAC) strongly expressed NRP1 on both tumor cells and endothelial cells, in contrast to other common cancer forms. Using proximity ligation assay, VEGFR2/NRP1 trans ‐complexes were identified in human PDAC tumor tissue, and its presence was associated with reduced tumor vessel branching, reduced tumor cell proliferation, and improved patient survival after adjusting for other known survival predictors. We conclude that VEGFR2/NRP1 trans ‐complex formation is an independent predictor of PDAC patient survival. © 2018 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.